Cross-Sectional Study on the Gut Microbiome of Parkinson’s Disease Patients in Central China - Mao, Liangwei; Zhang, Yu; Tian, Jing; Sang, Ming; Zhang, Guimin; Zhou, Yuling; Wang, Puqing (Frontiers in Microbiology, 2021)
Gastrointestinal dysfunction plays an important role in the occurrence and development of Parkinson’s disease (PD). This study investigates the composition of the gut microbiome using shotgun metagenomic sequencing in PD patients in central China. Fecal samples from 39 PD patients (PD group) and the corresponding 39 healthy spouses of the patients (SP) were collected for shotgun metagenomics sequencing. Results showed a significantly altered microbial composition in the PD patients. Bilophila wadsworthia enrichment was found in the gut microbiome of PD patients, which has not been reported in previous studies. The random forest model, which identifies differences in microbiomes, reliably discriminated patients with PD from controls; the area under the Receiver Operating Characteristic curve (ROC-AUC) was 0.803. Further analysis of the microbiome and clinical symptoms showed that Klebsiella and Parasutterella were positively correlated with the duration and severity of PD, while hydrogen-generating Prevotella was negatively correlated with disease severity. The Cluster of Orthologous Groups of protein (COG) database, the KEGG Orthology (KO) database, and the carbohydrate-active enzymes of gene-category analysis showed that branched-chain amino acid-related proteins were significantly increased and GH43 was significantly reduced in the PD group. Functional analysis of the metagenome confirmed differences in microbiome metabolism in the PD group related to short chain fatty acid precursor metabolism.